Environmental benefit analysis of "road-to-rail" policy in China based on a railway tunnel measurement. (20th September 2021) - Tong, Hui; Peng, Jianfei; Zhang, Yanjie; Fang, Tiange; Zhang, Jinsheng; Men, Zhengyu; Liu, Yan; Wu, Lin; Wang, Ting; Ren, Fumin; Xu, Honglei; Wang, Weichao; et al.
Abstract: The substitution of long-distance road transportation by railways, so-called the "road-to-rail" policy, is one of the major national regulatory policies for atmospheric pollution mitigation in China. However, owing to the lack of real-world diesel locomotive emission measurements, the environmental benefits of the "road-to-rail" policy have not been well evaluated. In this study, emissions from 245 in-use line-haul diesel locomotives (including three types of DF4, HX3, and HX5) were measured under real-world conditions via a railway tunnel observation conducted in Beijing on September 7–13, 2017. The fuel-specific and distance-specific emission factors (EFs) of NOx, CO, SO2, and BC were determined by using the carbon balance and mass conservation methods, respectively. The measured EFs of NOx and CO for the HX series locomotives were 41% and 30% higher than the Tire 2 emission standard limits respectively. Based on the two sets of EFs and corresponding activity levels, total locomotive emissions of NOx and CO in China in 2018 were approximately 17.36–19.23 × 10 4 t and 4.76–5.69 × 10 4 t respectively. Scenario analysis based on the fuel life cycle shows that all "road-to-rail" scenarios reduce the total energy consumption and pollutant emissions in the short term. For the scenario maintaining the current proportion (20%) of diesel locomotives, the "road-to-rail" policy may reduce NOx and BC emissions by 7.03–70.33 × 10 4 t/year and 0.10–1.02 × 10 4 t/year respectively. Considering the upgradation of emission standards with heavy-duty diesel vehicles, the air quality improvement benefit of the "road-to-rail" policy may only be sustained for 2–3 years and 8 years respectively, under the full diesel locomotive scenario and the current diesel locomotive scenario. We highlight the necessity of a more careful and accurate estimation of "road-to-rail" policy environmental benefits to obtain better air quality and the greatest health benefits. Graphical abstract: Image 1 Highlights: Emission factors of diesel locomotives are obtained via a railway tunnel study. Emissions of freight locomotives are higher than the Tire 2 standards. The road-to-rail policy achieves short-term huge environmental and climate benefits. The long-term environmental benefits of road-to-rail may disappear.